2004
DOI: 10.1002/hipo.20019
|View full text |Cite
|
Sign up to set email alerts
|

Theta reset produces optimal conditions for long‐term potentiation

Abstract: Connections among theta rhythm, long-term potentiation (LTP) and memory in hippocampus are suggested by previous research, but definitive links are yet to be established. We investigated the hypothesis that resetting of local hippocampal theta to relevant stimuli in a working memory task produces optimal conditions for induction of LTP. The timings of the peak and trough of the first wave of reset theta were determined in initial sessions and used to time stimulation (4 pulses, 200 Hz) during subsequent perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 25 publications
6
88
1
Order By: Relevance
“…Theta appears to reset its phase during the encoding of new stimuli (33), and it has been argued that this reset provides the basis for enhanced plasticity (13). These findings in rodents support the idea that the phase of theta oscillations provides a temporal separation of encoding and retrieval operations (34).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Theta appears to reset its phase during the encoding of new stimuli (33), and it has been argued that this reset provides the basis for enhanced plasticity (13). These findings in rodents support the idea that the phase of theta oscillations provides a temporal separation of encoding and retrieval operations (34).…”
Section: Discussionmentioning
confidence: 55%
“…Recent observations that perception of a stimulus can be influenced by prestimulus brain activity (10,11) raise the additional possibility that the brain state immediately preceding an event could predict later episodic memory. This possibility is supported by findings in rodents that the amplitude of hippocampal theta (3)(4)(5)(6)(7)(8) oscillations, which are held to be important modulators of the induction of synaptic plasticity (12)(13)(14), is associated with enhanced learning in classical conditioning even before stimulus onset (15)(16)(17). Because the medial temporal lobe (MTL) and, in particular, the hippocampus are also critical for episodic memory encoding in humans (18)(19)(20), prestimulus mediotemporal theta states might be linked to effective episodic memory encoding.…”
mentioning
confidence: 88%
“…The high phase-locking of u-band responses in the Trough group resembles the u reset observed in the dentate gyri of rats performing a working memory task involving both visual and auditory peripheral stimuli (Givens 1996). It has been demonstrated in rats that LTP is preferentially induced if stimulation is timed to occur during the peak of the CA1 u (trough of fissure u) not only when the oscillation occurs spontaneously (Holscher et al 1997) but also when it is evoked and reset by a peripheral stimulus (McCartney et al 2004). Thus, phase-locking or resetting of hippocampal u oscillation to the stimulus onset creates windows of opportunity for enhanced processing of subsequent relevant stimuli.…”
Section: Discussionmentioning
confidence: 77%
“…5B), illustrating that the LFP theta-phase resets of the theta-gamma-correlated network also indexed whether attention shifts are successful. A plausible mechanism for such a farreaching consequence of phase-aligned theta activation can be found in recent studies that identified how a cue-induced phase reset effectively gates the outflow of a cortical circuit (35)(36)(37). These studies suggest that the phase reset-gated output of a local circuit can serve as the causal trigger of distant gamma activity phase locked to theta activity.…”
Section: Discussionmentioning
confidence: 99%
“…We thus correlated burst-LFP synchronization of neurons recorded at LFP recording sites that provided theta-phase or gamma-amplitude variations for theta-gamma correlations (SI Result S13). We found that burst synchronization to remote LFP gamma activity varied proportionally with the degree of theta-phase correlation with low-gamma amplitudes (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), an effect that was limited to those LFP sites that showed significant theta-gamma correlations (Spearman rank correlation r = 0.2, P = 0.044; Table S2 and SI Result S13). To our knowledge, these findings provide the first quantitative evidence that recording sites with LFP theta phases that engage in longrange gamma correlations also host neurons whose burst firing events synchronize long-range to gamma activity.…”
Section: Theta-gamma Correlation and Its Relation To Synchronization Ofmentioning
confidence: 95%